2022
DOI: 10.1021/acssuschemeng.2c00054
|View full text |Cite
|
Sign up to set email alerts
|

Phenylphenothiazine-Based Porous Organic Polymers as Visible-Light Heterogeneous Photocatalysts for Switchable Bromoalkylation and Cyclopropanation of Unactivated Terminal Alkenes

Abstract: We report the design and synthesis of porous organic polymers (POPs) based on N-phenylphenothiazine (PTH), which typically requires ultraviolet-light irradiation, as a class of purely organic, stable, and reusable visible-light heterogeneous photocatalysts. The extended π-conjugation and polymeric networks not only enhance visible-light absorption but also accelerate the reaction rates. More intriguingly, the switchable bromoalkylation and cyclopropanation of unactivated terminal alkenes could be achieved by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…An ionic-liquid mediated methodology was adopted for the synthesis of g-CN catalysts and claimed that the procedure can be extended for the incorporation of heteroatoms into the g-CN morphology to conveniently tune the surface properties according to the requirement [ 120 ]. Metal-free PCN was also used for the gram-scale synthesis of tert - benzylic alcohols in a photocatalytic oxidation reaction [ 121 ]. In another report, Geng et al have successfully developed a metal-free g-CN catalyst for the synthesis of biologically valued isochromannones, phthalides, isoquinolinones, isoindolinones and xanthones from readily accessible alkyl aromatic precursors in good yields mediated by visible light.…”
Section: Prominent Catalysis Using Carbon Nitridementioning
confidence: 99%
“…An ionic-liquid mediated methodology was adopted for the synthesis of g-CN catalysts and claimed that the procedure can be extended for the incorporation of heteroatoms into the g-CN morphology to conveniently tune the surface properties according to the requirement [ 120 ]. Metal-free PCN was also used for the gram-scale synthesis of tert - benzylic alcohols in a photocatalytic oxidation reaction [ 121 ]. In another report, Geng et al have successfully developed a metal-free g-CN catalyst for the synthesis of biologically valued isochromannones, phthalides, isoquinolinones, isoindolinones and xanthones from readily accessible alkyl aromatic precursors in good yields mediated by visible light.…”
Section: Prominent Catalysis Using Carbon Nitridementioning
confidence: 99%
“…Finally, the enolate 124 underwent SET oxidation by Ru III and then the ring closed via a S N 1 reaction. Recently, Zhang's group designed and developed porous organic polymers (POPs) based on N‐phenylphenothiazine (PTH) [65] . The photochemical cyclopropanation of unactivated terminal alkenes with diethyl 2‐bromomalonate could be realized under the PTH‐POP catalysis.…”
Section: Photocatalytic Cyclopropanation Involving Radical Mechanismmentioning
confidence: 99%
“…As 3PTZ does not absorb photons in the visible region (Figure S1), the requirement of using UV irradiation might be problematic. On the other hand, it has been shown that polymerization of organic molecules can induce red shift in the absorption of wavelengths. , Inspired by these pioneering reports, we envisioned that cross-linking of 3PTZ could provide an advantageous option. Here, we report a 3PTZ-based porous framework (3PTZ-POP) synthesized via cross-linking of 3PTZ functions as a highly efficient, metal-free, and recyclable visible-light-active photocatalyst. The synthetic utility of 3PTZ-POP has been demonstrated in the sequential C­(sp 2 )–H functionalizations of N -arylacrylamides, where consecutive C–C bonds coupled with an all-carbon quaternary center were constructed in a single operation (Scheme ).…”
Section: Introductionmentioning
confidence: 97%